PERBEDAAN WARNA PERANGKAP POHON LALAT TERHADAP JUMLAH LALAT YANG TERPERANGKAP DI TEMPAT PEMBUANGAN AKHIR (TPA) SAMPAH JATIBARANG KOTA SEMARANG - Muhammad Arief Munandar; Retno Hestinigsih; Nissa Kusariana (Jurnal Kesehatan Masyarakat (Undip), 2018)
Flies are mechanical vectors of  transmitters. Phototropic’s characteristics of flies are they have a response to light, so the color produced from the reflection of light waves can be used for fly control. The objective of this study is to analyzed the differences in the color of a trap tree flies on the number of flies trapped in Jatibarang landfill Semarang. This research is a quasi experiment with the design of post test only control group design approach. The colors that used in this research on the range of light waves that can be responded by insects include flies ranging from 300-650 nm are a red, yellow, purple and white. Black used as a control because it does not reflect the light at all. The object of this research is the number of flies trapped in each color on the trap tree flies which placed around the Jatibarang landfill Semarang. The highest in red is about 207 because it has a high enough light waves but still included in the range of light waves that can be responded by flies. The number of flies which attached in yellow is 147; purple 121; white 162; and black (control) 144. Based on the results of statistical tests, showed that there are differences in the number of flies trapped in red tree traps is more closer than the other colors. However, the black as a control on the flies tree trap are still attended by flies although the black object does not reflect light at all. Therefore, further research is needed to do so.